2010
DOI: 10.1007/s00104-010-1933-3
|View full text |Cite
|
Sign up to set email alerts
|

Laparoskopische Reparation der parastomalen Hernie

Abstract: Parastomal hernias are a common complication after stoma formation. An exact evaluation of the history of the patients reveals clinically impairing symptoms in the majority of patients. The surgical treatment should generally be based on the augmentation or even replacement of the abdominal wall by non-resorbable meshes. The laparoscopic repair can be performed using the intraperitoneal placement of a mesh according to Sugarbaker with a wide lateralization of the stoma loop, the keyhole-technique, which means … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“…The number of cases of intestinal damage reported in papers ranges from approx. 2% (94,95) to even 10-20%. In Hansson's study intestinal damage rate was 10.9%, in case of primary hernias and even 20% in case of recurrent hernias (96).…”
Section: Intestinal Damage Caused During Surgerymentioning
confidence: 96%
See 2 more Smart Citations
“…The number of cases of intestinal damage reported in papers ranges from approx. 2% (94,95) to even 10-20%. In Hansson's study intestinal damage rate was 10.9%, in case of primary hernias and even 20% in case of recurrent hernias (96).…”
Section: Intestinal Damage Caused During Surgerymentioning
confidence: 96%
“…It seems, however, that the mesh should be shaped with a margin of at least 5 cm around the stoma -as in classical abdominal hernia surgeries. In one study, specially shaped implant attached laparoscopically inside the peritoneum demonstrated a 100% efficiency, which might prove its usefulness in hernia prevention (95).…”
Section: Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…Ziel der Untersuchung war die Klärung der Frage, ob die laparoskopische Kontinuitätswiederherstellung bei operativen Schwierigkeiten, wie veränderten anatomischen Gegebenheiten, bei ausgepräg-ten interenterischen Adhäsionen, fehlenden Grenzschichten und kompromittierten Durchblutungsverhältnissen bei vorhergehender Resektion der A. rectalis superior oder A. mesenterica inferior [9] sicher durchführbar ist und zur Senkung der hohen Morbidität und potenziellen Letalität dieses Eingriffs beitragen kann [6,10,11]. (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Es gab keine peri- oder postoperative Letalität.…”
Section: » Ein Enterostoma Bedeutet Für Die Betroffenen Eine Erheblicunclassified
“…Postope ratively, three (15.7%) minor complications (2× pneumonia, 1× protracted intestinal atonia) and four (21%) major complications requiring surgical intervention (2× wound infection, 1× adhesion ileus and 1× trocar site hernia) were observed. The median follow-up was eight (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) months. There were no peri- or postoperative mortalities.…”
Section: Schlüsselwörtermentioning
confidence: 99%